Reflections on music, health and spirituality - Ribeiro Leão, Eliseth (O Mundo da Saúde, 2007)
Spirituality is a human dimension frequently neglected in health care although being vital to health. Approaching it is a complex task, and we need to understand it better, as well as developing the ability to recognizing the spiritual needs of patients and implementing effective care forms. This article presents reflections on music, on its integrative character, and suggests its use as a resource that can assist in the understanding of the spiritual aspects and the sense of life.